Monkeypox: A resurfacing threat and global public health challenge in India - Saravanan S Pape Reddy; Delfin Lovelina Francis (Journal of Global Health Economics and Policy)
The global monkeypox outbreak presents a significant public health challenge, particularly in India, due to its rapid spread and the complexities of controlling transmission. This commentary discusses the epidemiological trends, transmission dynamics, and the challenges faced in managing the outbreak. Adopting a multidisciplinary approach, it reviews available data and literature on the spread and control of monkeypox, examining current surveillance systems, public health preparedness measures, and strategies employed to contain the disease. The review indicates that while efforts are underway to manage the outbreak, significant gaps remain in global surveillance and preparedness. The lack of targeted vaccination strategies and inconsistent public health responses exacerbate the difficulty of controlling monkeypox. Additionally, notable gaps persist in understanding its full transmission dynamics. The commentary calls for enhanced surveillance systems, improved public health preparedness, and the development of targeted vaccination strategies to mitigate the spread of monkeypox. It also emphasizes the need for a coordinated global response to emerging infectious diseases and proposes a more integrated, multidisciplinary approach to strengthening global health collaborations.